Perlindungan Hukum bagi Notaris dalam Melegalisasi Akta Dibawah Tangan yang menjadi Objek Sengketa - Ida Ayu Chandra Cintiadewi; I Nyoman Putu Budiartha; Ni Gusti Ketut Sri Astiti (Jurnal Preferensi Hukum, 2020)
A notary public genuinely serves as a public official appointed directly by the state, of which the authority is to make a deed as regulated in Notary Position Act (in Indonesian called UUJN-P). In addition to the main duty of making an authentic deed, the notary has the authority to legalize the deed made under the hand. Legal protection for Notaries is regulated in Article 66 of UUJN-P. This study aims to put up a standpoint of the legal regulatory concerning the authority of a Notary in making the deed under the hand which is the object of a dispute and legal protection for the Notary concerned in legalizing the mentioned deed. Using normative research method supported by empirical data, the results of the study show that, firstly, regarding the Notary authority in making a deed is divided into two, an authentic deed (notarial deed) and a deed under the hand. In the legal power of its evidence in court, a deed made under the hand can be evidence according to Article 1866 BW, but is not as perfect as an authentic deed because when the formal and material conditions of the agreement are recognized by the parties, since then the power of the deed under the hand becomes a strong evidence in the court. Secondly, legal protection can be realized through preventive and repressive efforts, but what is regulated in UUJN-P is not comprehensive yet it only protects the outside, a deadline indicates a weakness to protect. Making new regulations or adding clear elements of legal protection can clarify the position of the Notary to protect themselves in a conflict that results in litigation aimed at maintaining the honor of the Notary profession in society.